Some Legal Pitfalls for Writers - Lozanova, Ina (Yearbook of the Law Department, 2020)
The current article aims to outline some tort liability issues which can arise out of the description of actual persons and events in works of fiction. The material presents disputes from the US legal practice for libel and defamation in literary texts. Further, the possible development of hypothetical cases according to the Bulgarian legislation is reviewed.